2017
DOI: 10.1002/cnma.201700249
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Core‐Frame and Frame Multimetallic Rhombic Dodecahedra: A Comparison Study of Composition and Structure Effects on Electrocatalysis of Methanol Oxidation

Abstract: The composition and structure of multimetallic nanostructures can be tailored to enhance electrocatalytic properties. This work reports a seed-mediated synthesis of novel multimetallic dendritic core-frame and frame nanostructures with a rhombic dodecahedral shape for enhanced methanol oxidation reaction (MOR). The synthesis involves in situ formation of Cu seeds and the subsequent selective deposition of Pt and Ru on the edges and vertices of the Cu seeds to generate CuPt and CuPtRu dendritic core-frame nanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…The Ru 3p 3/2 BE of br ‐CuPtRu was slightly upshifted compared to that of sr ‐CuPtRu, indicating that br ‐CuPtRu contained less oxidized Ru than sr ‐CuPtRu. This result suggests that Ru in the alloy is more stable than itself against oxidation and thus prevents leaching from the catalyst surface . This finding agrees with the higher stability of br ‐CuPtRu than that of sr ‐CuPtRu.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…The Ru 3p 3/2 BE of br ‐CuPtRu was slightly upshifted compared to that of sr ‐CuPtRu, indicating that br ‐CuPtRu contained less oxidized Ru than sr ‐CuPtRu. This result suggests that Ru in the alloy is more stable than itself against oxidation and thus prevents leaching from the catalyst surface . This finding agrees with the higher stability of br ‐CuPtRu than that of sr ‐CuPtRu.…”
Section: Resultssupporting
confidence: 81%
“…The high value of sr ‐CuPtRu had a very steep drop to 0.006 A mg Pt −1 within the first 50 s and levered at 0.005 A mg Pt −1 for the rest of the measurement up to 1800 s. The poor stability of sr ‐CuPtRu is attributed to the phase segregation of Ru on the catalyst surface which is easily leached from the catalyst surface, leaving behind the less electrochemically active bimetallic CuPt. In contrast, the high value of br ‐CuPtRu exponentially dropped to 0.025 A mg Pt −1 in 500 s, but leveled off and maintained at 0.018 A mg Pt −1 during the measurement up to 1800 s. These results suggest that the trimetallic surface alloy on br ‐CuPtRu with larger ECSA not only enhance the catalyst activity for MOR but also reduce the dissolution of Ru from the alloy for improving stability of the catalyst …”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The open frame structures were more active catalysts than the solid nanoparticles for alcohol oxidations [16,35,36]. We demonstrated that other nanostructures with highly accessible surfaces including Pt-Cu nanodendrites [37], nanowires [38], core-frame and frame structures could enhance MOR activity [39]. In this work, we reported a seeded co-reduction method to synthesize the rhombic dodecahedral, hierarchical structure.…”
Section: Introductionmentioning
confidence: 92%